Accelerated life cycle tests of catenary supports of railways - A. A. Tsar’Kov; P. G. Tyurnin; D. V. Tartynskiy; V. V. Ivakin (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
The large base of support of catenary supports on railways sets urgent task to assess their condition and load capacity. Condition of catenary supports evaluated during operation. In addition to the existing supports on the railways there are new types, such as supports, manufactured using composite materials. To confirm their reliability and performance in terms of rail transport it is necessary to carry out complex tests. Tests are offered to perform in two stages: 1) bench tests to check mechanical properties and geometrical indicators; 2) accelerated life cycle testing. Accelerated life cycle tests are divided into bench and operational. For the bench accelerated tests a stand for vibration loading of racks of catenary supports is designed, which allows carrying out tests to determine resistance of supports to vertical vibration, resistance to relative creeping of racks. The stand has the ability to create static loading for racks of catenary supports up to 40 kN and dynamic loading up to 10 kN at a frequency of applying loads up to 5 Hz. Description and the scheme of the stand of vibration loading for racks of catenary supports are provided in article. Parameters of vibration loading are chosen. The technique of carrying out accelerated life cycle tests is offered. The technique of vibration loading is given. Bench tests of racks for catenary supports by the offered technique allow giving an assessment to a possibility of application of new types of supports in the conditions of railway operation.